26 A HUMAN-ASSOCIATED FECAL TRANSPLANTATION MOUSE MODEL TO STUDY THE FUNCTIONALITY OF THE GUT MICROBIOME. (18th January 2018) - Basson, Abigail R; Gomez-Nguyen, Adrian; Buttó, Ludovica; Menghini, Paola; Martino, Luca Di; Lam, Minh; Aladyshkina, Natalia; Rodriguez-Palacios, Alexander; Cominelli, Fabio
Abstract: Background: We performed a series of fecal microbiota transplantation (FMT) experiments to determine the functional persistence of human microbiota in our gnotobiotic (hGB) SAMP1/YitFc (SAMP) mouse model of Crohn's disease (CD)-like ileitis. Methods: Groups of sex-matched, 7-wk-old SAMP mice (i.e. before ileitis onset), were inoculated with 200μl (10 ˆ 8–9 CFU) of fecal microbiota from different inflammatory bowel disease (IBD) (CD, UC; ulcerative colitis) or healthy non-IBD individuals (N=12), or specific pathogen-free (SPF) SAMP1 mice, for 8 weeks. Separate FMT experiments tested the effect of 3% dextran sodium sulfate in SAMP. Illumina 16S rRNA gene sequencing and PICRUSt software (v1.1.1) was used to connect differences in the functional composition of fecal samples with phenotypic and extensive immunological parameters in groups. All evaluations were performed blinded. Results: Histological and 3D-stereomicroscopic assessments revealed hGB mice treated with one specific non-IBD inoculum results in prevention of CD-like ileitis, significantly higher IL-10 tissue culture levels, and gene expression in MLN (vs other groups). Microbiota from other human donors (IBD, non-IBD) resulted in ileitis development after FMT. Principal component analyses demonstrated strong microbiome segregation among FMT groups. Pairwise ß-diversity showed stability of microbial community structure starts from day 4; hGB groups had between 1 and 7 genus-level taxa missing, of which, all were present <0.007% relative abundance in their original donor sample. Opposing, yet stable, significant differences in inferred metagenomes between FMT groups were identified, specifically in genes for biosynthesis, degradation, and metabolism of fatty acids, carbohydrate derivatives, tryptophan, and sulfur (oxidative stress). Conclusion: Our results show stability of microbiota in hGB SAMP mice, and suggest, bacterial species and associated metabolites, successively contribute to altering immune pathways.